Exchange Rate Changes and Trade Flows in East Asia - Jerome Terhemba Andohol; Victor Ushahemba Ijirshar; Oluwafemi David Ogunjemilua; Solomon Gbaka (Scientific Annals of Economics and Business, 2024)
This study investigates the impact of exchange rate changes on trade flows among East Asian countries spanning 1990–2021, using pooled mean group estimator, within the framework of panel data analysis. Findings indicate that world income, trade openness, and the real effective exchange rate strongly affect trade balance, and that the real depreciation of exchange rate exerts strong positive benefits on trade flows in the long run. The study also infers that trade openness and real effective exchange rate had strong influence on exports and imports for Hong Kong, Japan, and South Korea in the short run. However, the depreciation of their currencies discouraged imports in the long run. More so, world income strongly affects the exports and imports of Hong Kong and Japan, while trade openness is advantageous for all the countries. The study recommends the continuation of the prevailing trade-growth pattern, and the existing bilateral pegged exchange rate policy with their trading partners.